KOMPARASI KUALITAS CITRA HASIL REKONSTRUKSI METODE ALGEBRAIC RECONSTRUCTION TECHNIQUE (ART) ADITIF DAN MULTIPLIKATIF (MART) PADA CT SCAN - Anam, Choirul; Firdausi, K Sofjan (BERKALA FISIKA, 2011)
AbstractImage recontruction for CT scan by the methods of additive ART and muliplicative ARTÂ (MART) have been carried out using Malab software. The object used is Sheep-Logan phantomwith matrix size 50x50, Â used a paralel beam and Â angle interval 10, 50, 10,respectively. It is obtained that additive ART produces many artifacts, while MART producesfewer artifacts. Additive ART produces a contras between objects and background with relativelyhigh, while MART produces relatively lower contrast. It is obtained that in the additive ART,interval angle affects the quality of image. This does not happen to MART. So, the MARTreconstruct CT image faster, because it can be obtained relatively good image despite the angleinterval is large.Keywords: Image reconstruction, Additive ART, Multiplicative ART (MART)